Calcareous nannoplankton in Cretaceous rocks of the north-west part of the Crimean continental slope - Matlaj, L.M. (Reports of the National Academy of Sciences of Ukraine, 2016)
The calcareous nannoplankton is first studied in the Cretaceous rocks of the Crimean continental slope at stations 3-27, 5806, 5862, 5746, 5604. The associations of a calcareous nannoplankton of the Jurassic, Aptian, Albian-Cenomanian, Coniacian-Santonian ages are defined. The most favorable conditions for the existence of a calcareous nannoplankton were formed in the Late Albian — Early Cenomanian.